The Emergence of Crack Cocaine and the Rise in Urban Crime Rates - Grogger, Jeff; Willis, Michael (The Review of Economics and Statistics, 2000)
Despite widespread popular accounts that link crack cocaine to inner-city decay, little systematic research has analyzed how the emergence of crack affected urban crime. We study this question using FBI crime rates for 27 metropolitan areas and two sources of information on when crack first appeared in those cities. Using methods designed to control for unobserved differences among metropolitan areas, we find that the introduction of crack had substantial effects on crime. In the absence of crack cocaine, the 1991 peak in urban crime rates would have been approximately 10% lower, remaining below the previous peak levels of the early 1980s.